Hybrid Electric Vehicle: An Overview of Technology - Uddhav P. Aher; Krishna T. Madrewar (International Journal of Electrical Power and Machine Systems, 2024)
This article examines and explains the many HEV architectures and operating concepts, including as series hybrids, parallel hybrids, and series-parallel hybrids. The function of regenerative braking in hybrid electric vehicles (HEVs) is also covered; it allows energy to be recovered during braking and deceleration, improving total energy efficiency. The article also looks at key issues including battery technology, energy management plans, and powertrain integration that need to be considered while building hybrid electric cars. It also showcases developments in the sector, like plug-in hybrid electric cars (PHEVs), which allow for external charging and provide an expanded driving range when using only electricity. The advantages of hybrid electric vehicles for the environment are discussed, with a focus on how they can lessen reliance on fossil fuels and greenhouse gas emissions. There is also discussion of the financial issues, such as the price and market acceptance of HEVs.
Keywords: Electric vehicle; ICE; battery; charging; efficiency; hybrid vehicle; traction motor